Zero rating and end-users' freedom of choice: An economic analysis - Laure Jaunaux; Marc Lebourges (International Telecommunications Society (ITS), 2018)
According to Open Internet Regulation, commercial practices of Internet access Service Providers (ISP) should not restrict end-users' rights regarding services, applications or contents. This paper analyses specifically if zero rating (ZR) enhances or restricts end-users' choice translating this regulatory criterion into a formal expression: providing a zero rating offer on a content or application provider (CAP) will be considered as restricting end-users' choice if it has the direct or indirect effect of reducing the usage or provision of other CAP's non-zero rated services, all other things being equal. This article shows that in the short term, with the ISP offer unchanged, adding a zero rating service tends not to directly restrict end-users' choice, increasing both zero rated and non-zero rated usages. In the long term, ISPs may adapt their offer to support the cost of zero rating and it could in principle have a negative indirect impact on the usage of non-zero rated services if the zero rated traffic is financed by the ISP. However, in practice any such negative effects of zero rating are diluted or compensated by competitive forces in the absence of dominance in the ISP and CAP markets or if the volume of zero rated traffic is small compared to the data allowance available to the end user. A contrario, in the case of sponsored data, the corresponding traffic cost is covered by the CAP. It prevents any need for cross-subsidies and therefore protects end-users' freedom of choice, to the extent that the ability to sponsor data is opened to all content and application providers on equivalent terms.
Keywords: 330; Telecoms regulation; Net neutrality; Zero rating